EFEKTIFITAS SOFTWARE PENGOLAH HASIL TES FISIK CABANG OLAHRAGA BOLA VOLI PADA PELATIH BOLA VOLI DI PEKANBARU - Pratama Anugerah Putra; Ni Putu Nita Wijayanti; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study uses a Likert scale using a Likert scale model consisting of a scale of 4 answers. The nature of the contents of this questionnaire is divided into 2 types, positive and negative. Each answer given by the respondent has a different weight value (%), including strongly disagree (10%), disagree (20%), agree (30%), and strongly agree (40%). From the results of the research that has been carried out, it can be concluded that the software for processing the results of the physical test of volleyball sports is effectively used where the results of the research with statistical calculations using SPSS 25 by testing the validity of r arithmetic > from r table (0.878) are declared valid, 8 items statement is declared valid. Furthermore, the reliability test where r alpha > 0.600 is declared reliable, so the 8 statement items get a reliable result of 1,000. And the results of the questionnaire calculation, respondents who answered positive items amounted to 54.68% plus the results of the calculations of respondents who answered negative items amounted to 28.75%, namely the sum of 83.43%, where the very good range was at 75.01 - 100% . And based on hypothesis testing which was measured using SPSS version 25, the method used to see the results of the paired sample t-test was if the value of sig.(2-tailed) < 0.05 then there was a significant difference. If the value of sig.(2-tailed) > 0.05 then there is no significant difference. Based on the calculation of the paired sample t-test, it is known that the value of sig. (2 tailed) is 0.000 <0.05, it can be concluded that there is a significant difference between manual time and sports application software. This proves that the athlete's physical test data processing is effective compared to using manual data processing on volleyball coaches in Pekanbaru.Key Words: Effectiveness of Physical Test Result Processing Software, Volleyball Player